Effectiveness of Soil Moisture Conservation Practices in Enhancing the Productivity of Sorghum Under Rainfed Cropping System in Semiarid Climate Type of Babile District, Eastern Ethiopia - Abdisa Alemu Tolossa; Diriba Korecha Dadi; Lemma Wogi Mirkena; Zelalem Bekeko Erena; Feyera Merga Liben (Advances in Agriculture)
To grasp how soil moisture conservation techniques can lessen the effects of dry spells in moisture-stressed areas, we carried out a field experiment using a randomized complete block design (RCBD). The study took place in the Babile district over the 2021 and 2022 cropping seasons, involving six treatments across three replications. Each plot measured 4.2 by 5.4 m. The treatments were (A) Zai pit, (B) closed end Tied ridge, (C) flatbed (control) with sorghum, (D) Zai pit with legume cover cropping, (E) closed end Tied ridge with legume cover cropping, and (F) flatbed with legume cover cropping. We analyzed grain yield variance (analysis of variance [ANOVA]) and accumulated rainfall amounts throughout the experiment. Our results indicated that rainfall during the cropping seasons was 410 mm over 35 days in 2021 and 213 mm over 18 days in 2022. The grain yield from the Tied ridge moisture conservation practice was recorded at 6.85 t/ha in 2021 and 5.72 t/ha in 2022 at the Babile site, compared to yields of 4.75 t/ha in 2021 and 2.99 t/ha in 2022. When comparing the Zai pit with legume cover cropping (4.44 t/ha) to those without (4.25 t/ha), no significant differences were found. However, the mean grain yield from Zai pit practices was notably lower than that from the Tied ridge practices but higher than both variations of flatbed farming practices. Across the combined sites and seasons, the average sorghum grain yields were 5.07 t/ha for Tied ridge with cover cropping, 4.65 t/ha for Tied ridge without cover cropping, 3.65 t/ha for Zai pit with legume cover cropping, 3.52 t/ha for Zai pits without legume cover cropping, 3.12 t/ha for flatbed with legume cover cropping, and 3.07 t/ha for flatbed without legume cover cropping (control). The treatment effects on grain yield showed a highly significant variation (p <0.05), with Tied ridge practices yielding 2 t/ha more than control treatments. The use of legume covers cropping did not significantly alter the sorghum grain yield across all treatments. Nonetheless, Tied ridge treatments with legume cover cropping consistently produced higher grain yields compared to other practices at both experimental sites. In summary, our findings are valuable for assessing effective Tied ridge moisture conservation practices for enhancing crop production, underscoring the importance of raising awareness about these practices as a viable strategy to counteract the adverse impacts of dry spells.